Medicinal use of Samaúma (Ceiba pentandra): Literature review (Research, Society and Development, 2023)
Samaúma (Ceiba pentandra) is a tree that has many proven pharmacological properties, being used for the treatment of various pathologies. This work aimed to exhibit such properties in order to defend its usefulness in drug treatment, as well as to value the tree native to the Brazilian Amazon region and its therapeutic effects. From the research carried out, a bibliographical review was carried out, where articles and scientific publications were evaluated in order to find ways of how and when to use the plant for medicinal benefit, as well as to know the chemical properties that are part of the therapeutic process. According to the study carried out, samaúma holds several active principles capable of assisting in the treatment and recovery of pathologies, its various chemical compounds have proven efficacy in research and in vivo studies. Understanding the amount of pharmacological benefits delivered by samaúma, it is possible to conclude that the lack of studies focused on its use may mean a delay in phytotherapeutic pharmacology and phytopharmaceuticals, requiring greater emphasis on studies focused on Ceiba pentandra.